Pengembangan Media Buletin Berbasis Science, Environment, Technology and Society Pada Materi Keunggulan Nanomaterial Sebagai Implementasi Merdeka Belajar di Sekolah Penggerak - La Ode Muhammad Anzal Wahid Fariu; Muh. Alim Marhadi; Abraham Rahman (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2023)
The aim of this research is to determine the quality of the SETS-based bulletin learning media as well as the responses of teachers and students to the SETS-based bulletin learning media that was developed. This type of research is Research & Development (R&D) using the ADDIE development model. The instruments used were validation sheets and teacher and student response questionnaires. The sample for this research was class X students and 1 teacher. The research results showed that the SETS-based bulletin media for superior nanomaterials met the very valid criteria with a material aspect percentage of 84.1% and a media aspect of 82.8%. Teachers gave a very practical response to the media developed with a practicality score of 82.8%, while students had a practicality score of 87.5%. From the results of this research, it can be concluded that the SETS-based Bulletin Media on Nanomaterial Advantages developed has very good quality and can be used to support learning.